2015
DOI: 10.1177/0885412215589848
|View full text |Cite
|
Sign up to set email alerts
|

Do Clusters Encourage Innovation? A Meta-analysis

Abstract: This article carries out a meta-analysis on empirical studies addressing cluster–innovation relationships since the 1980s. The results show that (1) clusters have positive effects on innovation; (2) different studies demonstrate heterogeneity in the estimated effect sizes; (3) several moderators are shaping the cluster–innovation relationship, for example, in what industries the cluster specializes, in which geographical region the cluster is located, and so on. This article reveals the cluster–innovation rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 107 publications
0
48
0
3
Order By: Relevance
“…Fang (2015) identifie quatre avantages spécifiques : elles favorisent la productivité et l'efficience (en raison de la concentration géographique et des liens de collaboration); elles stimulent l'innovation et sa mise en oeuvre (grâce à la coopération et à la collaboration au niveau de l'entreprise); elles accentuent la compétitivité (grâce à l'augmentation susmentionnée de l'efficacité et de la capacité d'innovation; elles augmentent la croissance d'entreprises existantes et la création des start-ups. Fang (2015) identifie quatre avantages spécifiques : elles favorisent la productivité et l'efficience (en raison de la concentration géographique et des liens de collaboration); elles stimulent l'innovation et sa mise en oeuvre (grâce à la coopération et à la collaboration au niveau de l'entreprise); elles accentuent la compétitivité (grâce à l'augmentation susmentionnée de l'efficacité et de la capacité d'innovation; elles augmentent la croissance d'entreprises existantes et la création des start-ups.…”
Section: Les Fondements Théoriques De L'émergence Des Grappes Industrunclassified
See 1 more Smart Citation
“…Fang (2015) identifie quatre avantages spécifiques : elles favorisent la productivité et l'efficience (en raison de la concentration géographique et des liens de collaboration); elles stimulent l'innovation et sa mise en oeuvre (grâce à la coopération et à la collaboration au niveau de l'entreprise); elles accentuent la compétitivité (grâce à l'augmentation susmentionnée de l'efficacité et de la capacité d'innovation; elles augmentent la croissance d'entreprises existantes et la création des start-ups. Fang (2015) identifie quatre avantages spécifiques : elles favorisent la productivité et l'efficience (en raison de la concentration géographique et des liens de collaboration); elles stimulent l'innovation et sa mise en oeuvre (grâce à la coopération et à la collaboration au niveau de l'entreprise); elles accentuent la compétitivité (grâce à l'augmentation susmentionnée de l'efficacité et de la capacité d'innovation; elles augmentent la croissance d'entreprises existantes et la création des start-ups.…”
Section: Les Fondements Théoriques De L'émergence Des Grappes Industrunclassified
“…Les grappes industrielles procurent aussi des avantages significatifs aux entreprises regroupées au sein des celles-ci. Fang (2015) identifie quatre avantages spécifiques : elles favorisent la productivité et l'efficience (en raison de la concentration géographique et des liens de collaboration); elles stimulent l'innovation et sa mise en oeuvre (grâce à la coopération et à la collaboration au niveau de l'entreprise); elles accentuent la compétitivité (grâce à l'augmentation susmentionnée de l'efficacité et de la capacité d'innovation; elles augmentent la croissance d'entreprises existantes et la création des start-ups. En outre, les grappes influencent positivement le développement et la croissance économique des régions dans lesquelles elles s'insèrent en constituant un centre de gravité servant à attirer l'innovation, les compétences et les connaissances (Gilbert 2017).…”
Section: Les Fondements Théoriques De L'émergence Des Grappes Industrunclassified
“…Second, compared to a more geographically distant partner, a potential proximate partner is more apt to be familiar with an organization and in a better position to evaluate its technological resources and capabilities (Reuer and Lahiri, 2014). Third, research in economic geography has established that firms with specific products or activities are geographically unevenly distributed (Fang, 2015). As a consequence, the advantages of geographical proximity for partner selection accrue especially to firms located in denser clusters of firms, as they have a richer selection space.…”
Section: Proximity Hypothesesmentioning
confidence: 99%
“…Porter [27] noted that innovation and the commercialization of new technologies take place disproportionately in clusters. By doing a meta-analysis synthesizing 70 papers on the innovation-cluster relationship published from 1988-2014, Fang [28] found that except insignificant or mixed results, positive effects are reported two to three times more frequently than negative effects, based on which she concluded the generally positive effects of clusters on innovation. Some authors think innovation clusters are clusters accommodating innovative industries.…”
Section: Introductionmentioning
confidence: 99%